Questioning Strategies Used by an English Teacher in the Opening and Closing Sessions - Nailul Fauziyah; Janna Sinatriya Junaidi (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2021)
Questioning strategies is an important stage in teaching and learning activities. It will determine how the learning runs. A questioning strategy was used in the opening and closing of the speaking class. It can build student's motivation in following the learning process. The purpose of teachers questioning strategy in opening and closing at students. In the research of this study, it used qualitative research by (Nugrahani, 2014: 4). This study found the teacher mostly using descriptive and comparative questioning in opening and closing class in class XI Bahasa and XII MIA Jombang. The interview of the teacher was mostly using probing, whereas the observation was mostly using descriptive and comparative questions and did not use probing.